PAKET WISATA EDUKASI SUBAK UPAYA MENJAGA KEBERLANJUTAN POTENSI PERTANIAN DAN PARIWISATA BERBASIS BUDAYA DI BALI - Ni Luh Ramaswati Purnawan; I Ketut Sardiana (Jurnal Kawistara, 2017)
Tourism and agriculture are leading sectors of development in Bali Province. Before Bali’s economy relies heavily on tourism sector, agriculture was a major driver of economic growth. However, with so many challenges of land adjustment and use, and the increase tendency of agricultural land conversion into non-agricultural purpose, the growth of the agricultural sector gradually decreased. Declining of agriculture domain might cause a challenge for Bali because agriculture is not just an activity of land cultivation, but it has related more as spirit or the essential substances of Balinese cultural identity. One of the agricultural universal icons is the Subak system, which has named as world cultural heritage by UNESCO in 2012. Thus, to ensure the sustainability of the agricultural and tourism in Bali, the effort to combine both fields through development of Subak educational tourism becomes relevant. This idea is based on the perspectives that agricultural and tourism areas are interrelated systems. Tourism in Bali is counting on how Bali can preserve its natural and cultural attractions, this include the agrarian culture and lifestyle. The emergence of knowledge-based society, that encourage travellers to be actively involved and participate to fulfill their desire of learning and understanding others culture, has greatly contributed to development of this special interest tourism. Study indicated that Subak educational tourism can be applied toward sustainability as it incorporated the aspect of natural and socio-cultural conservation and could offer economic benefits for the well-being of the local community.